Effect of Different Organic Sources on the Productivity of Upland Terraced Rice (Oryza sativa L.) under Organic Farming in Nagaland - Rualthankhuma, C.; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was carried out in the experimental research farm of School of Agricultural Sciences and Rural Development (SASRD), Nagaland University during April to September, 2008 to study the Influence of organic sources of nutrients in enhancing productivity of upland rice (Oryza sativa L.). The treatments were vermicompost @ 3 t ha-1, Farmyard manure (FYM) @ 12 t ha-1, Vegetable sea weed manure (VSWM) @ 25 kg ha-1 + FYM @ 2 t ha-1, Azospirillum + FYM @ 9 t ha-1, Bio-activated algal sea weed manure (BASWM) @ 25 kg ha-1 + FYM @ 2 t ha-1, Azospirillum + Vermicompost @ 2.25 t ha-1 and control replicated thrice laid out in Randomized Block Design. The investigation revealed that application of Azospirillum + FYM @ 9 t ha-1 recorded Maximum (489.1 g, 146, 275) dry weight m-2, number of panicles m-2 and grains panicle-1 contributing to highest (28.17 and 56.27 q ha-1, respectively) grain and straw yield. Similarly, the same treatment also yielded highest (34.93, 29.26 and 188.2 kg ha-1, respectively) N uptake by grain and straw as well as available nitrogen